Pengaruh Green Packaging terhadap Keputusan Pembelian Melalui Persepsi Harga dan Kualitas Produk: Studi pada Konsumen Produk Mcdonald’ S di Kota Semarang - Nicholas Stevan Djajakusumah; Mahfudz Mahfudz (Faculty of Economics and Business Diponegoro University, 2026)
This study aims to analyze the effect of green packaging on price perception, product quality, and purchasing decisions of McDonald’s products in Semarang City. In addition, this study also examines the mediating role of price perception and product quality in the relationship between green packaging and purchasing decisions. The research method used is a quantitative approach with Structural Equation Modeling (SEM) analysis using AMOS software. The sample consists of 138 respondents who are McDonald’s consumers in Semarang City, selected using purposive sampling technique. The results show that green packaging has a positive and significant effect on price perception, product quality, and purchasing decisions. Price perception and product quality are also proven to have a positive and significant effect on purchasing decisions, where product quality has the most dominant influence. Furthermore, the mediation test results indicate that price perception and product quality are able to mediate the effect of green packaging on purchasing decisions. This indicates that the implementation of environmentally friendly packaging not only enhances product image but also influences consumers’ perceptions of price and quality, thereby encouraging purchasing decisions. This study implies that companies need to improve the implementation of green packaging consistently and communicatively in order to enhance consumer perceptions more effectively. In addition, companies should maintain product quality and ensure that pricing is aligned with the perceived benefits received by consumers. Future research is recommended to include additional variables such as brand image or customer satisfaction and to expand the research scope to obtain more comprehensive results.